Synthesis of highly electrochemically active Li2S nanoparticles for lithium–sulfur-batteries1. Issue 31 (21st August 2015) - Kohl, M.; Brückner, J.; Bauer, I.; Althues, H.; Kaskel, S.
<x xml:space="preserve">Abstract</x> Carbothermal reduction of lithium sulfate below its melting point was used to produce sub-micron sized lithium sulfide particles which retain the morphology of the source particle and achieve high discharge capacities up to 1360 mA h gsulfur−1.